2014
DOI: 10.1186/1747-597x-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Risk of anaphylaxis in opioid dependent persons: effects of heroin versus substitution substance

Abstract: Background: Across Europe, illicit drug-related mortality has not declined despite ever increasing prevention measures. The cause of these deaths has traditionally been associated with overdose. Previous findings have revealed the appearance of non-lethal opioid concentrations, leading us to investigate a further cause of death. The symptoms of heroin intoxication with asphyxia and/or cardiovascular involvement resemble anaphylaxis, and therefore it has been speculated that such deaths might be caused by an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Understanding PWID’ risk behavior in the context of the structural risk environment enables tailoring structural, behavioral and clinical interventions e.g., syringe exchange programs (Hurley et al, 1997) and harm-reduction oriented SSTI clinics (Grau et al, 2002; Harris and Young, 2002; Messac et al, 2013; Robinowitz et al, 2014). Future investigations into the causes of SSTI among heroin injectors should consider both physiological and chemical mechanisms, including the measurement of histamine as an injection induced inflammatory marker (Maurer et al, 2014), and drug solution acidity (Ciccarone and Harris, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Understanding PWID’ risk behavior in the context of the structural risk environment enables tailoring structural, behavioral and clinical interventions e.g., syringe exchange programs (Hurley et al, 1997) and harm-reduction oriented SSTI clinics (Grau et al, 2002; Harris and Young, 2002; Messac et al, 2013; Robinowitz et al, 2014). Future investigations into the causes of SSTI among heroin injectors should consider both physiological and chemical mechanisms, including the measurement of histamine as an injection induced inflammatory marker (Maurer et al, 2014), and drug solution acidity (Ciccarone and Harris, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The concentration that denotes elevation due to allergic reaction is not clear; a recent study suggests that 53.8 ng/mL may be an appropriate cut-off [14]. A significant mean baseline elevation of β mast-cell tryptase has been noted in opioid users, however (6.0 ± 4.3 ng/mL), compared to non-opioid users (3.9 ± 1.9 ng/mL), suggesting that the standard threshold used in this study was appropriate [3]. Some studies have furthermore shown that this analyte may be elevated in postmortem serum of persons from whom anaphylactic reactions are not the cause of death [15,16].…”
Section: Discussionmentioning
confidence: 94%
“…While prescription narcotic abuse is increasing, heroin is still common [1], and designer fentanyls are appearing in many areas [7]. Most fatalities from opioids are due to overdose, but deaths involving opioids with concentrations lower than those associated with fatality are common [3]. In this latter group with apparently sublethal concentrations of opioids, it can be difficult to interpret what the detected concentrations of opioids mean; pertinent factors that may be unanswerable even with comprehensive review of clinical history and medical records include individual tolerance of opioids or relative naïveté to the drugs; metabolism of the opioids if death is prolonged and the drugs remain as active metabolites; drug-drug interactions; and individual genetic factors, such as slow metabolizers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations